Physicochemical properties, structure and digestibility in simulated gastrointestinal environment of bread added with green lentil flour. (15th January 2022) - Gallo, Veronica; Romano, Annalisa; Miralles, Beatriz; Ferranti, Pasquale; Masi, Paolo; Santos-Hernández, Marta; Recio, Isidra
Abstract: Aim of this work was to evaluate the impact of bread enrichment with different concentrations of lentil flour (LF) (0 g/100g, 10 g/100g and 20 g/100g) on some physico-chemical, structural, and nutritional features of bread. The addition of LF in formulation affected its properties, leading to a darker appearance and to a more compact structure ( e.g., higher density and lower gas bubble area fraction). Besides, it led to a significant rise in the protein, free glucose, and rapidly digestible starch content as well as in the expected glycemic index. Concerning the investigation of nutritional properties, starch and protein digestibility has been evaluated by the combination of different digestion models. Each type of bread was subjected to an in vivo oral phase followed by a semi-dynamic in vitro gastrointestinal digestion. During the oral and the gastric phases of digestion, bread with the greatest LF content (20 g/100g) exhibited an extensive starch digestibility and a partial protein digestibility compared to the other samples, due to its higher protein content. In contrast, during the intestinal phase, control (0 g/100g) showed a stronger starch digestibility compared with the LF samples, while no differences could be observed in terms of protein digestibility investigated by SDS-PAGE. Highlights: The use of lentil flour (LF) affected physico-chemical properties of bread. The addition of LF increases the protein and free glucose content in wheat bread. LF-added samples showed a more compact structure than wheat bread. pH tracing during gastric digestion trials is useful to monitor protein hydrolysis. Increasing LF concentration in bread enhances its starch digestibility.